Fluctuating asymmetry of finger lengths, digit ratio (2D:4D), and tattoos: A pre-registered replication and extension of Koziel et al. (2010). (January 2021) - Osu, Tinisha; Lechler-Lombardi, Julia; Butler, Amy; Newman, Miles; Miłkowska, Karolina; Galbarczyk, Andrzej; Richards, Gareth
Abstract: Background: Tattoos bring risks yet no obvious evolutionary benefit. Koziel et al. (2010) reported increased fluctuating symmetry (a proxy for low developmental instability) in tattooed men, suggesting they could serve as fitness indicators. Aims: We replicate and extend the findings of Koziel et al. by examining fluctuating asymmetry of finger lengths and digit ratio (2D:4D) (a putative indicator of prenatal testosterone exposure) as predictors of adult tattoo prevalence. Study design: We used an online survey with a correlational design. Subjects: Participants were recruited from the UK and Poland via university participant pools and social media. Data were available for presence/absence of tattoos and at least one predictor variable (composite Fluctuating Asymmetry [cFA], right-hand digit ratio [R2D:4D] and left-hand digit ratio [L2D:4D]) for n  = 186 males and n  = 997 females. Outcome measures: We firstly assessed presence/absence of tattoos; when at least one tattoo was present, we also examined overall number and highest visibility. Results: Greater cFA was associated with lower likelihood of having tattoos in males, though in females greater cFA was associated with higher numbers of tattoos. R2D:4D and L2D:4D correlated negatively with number of tattoos in males, and a positive correlation between L2D:4D and number of tattoos was observed in females. However, these latter findings did not remain significant after controlling for covariates. Conclusions: Tattoos may act as fitness indicators in males, though this explanation appears not to extend to females. Prenatal testosterone may also play a role, though doubt is cast on this premise because 2D:4D effects did not remain statistically significant after controlling for covariates. Highlights: Tattoos may be associated with prenatal testosterone and used as fitness indicators. Koziel et al. (2010) reported increased bodily symmetry in tattooed males. We broadly replicate this previous finding in a large sample from the UK and Poland. Number of tattoos correlated positively with fluctuating asymmetry in females. Digit ratio (2D:4D) and tattoos were not associated when covariates were controlled.